Employment and related economic outcomes for Australian apprenticeship and traineeship graduates with disabilities: Baseline findings from a national three-year longitudinal study - Cocks, Errol; Thoresen, Stian; Lee, Elinda (IOS Press, 2013)
BACKGROUND: Apprenticeships and traineeships are beneficial vocational pathways for people with disabilities as they include work-based training and provide nationally recognised formal qualifications. While vocational education and training (VET), particularly apprenticeships and traineeships, has been found to benefit people with disabilities, graduate outcomes are not well documented over time.OBJECTIVE: Identify economic and related outcomes among a cohort of apprenticeship and traineeship graduates with and without disability in Australia from a prospective longitudinal study.METHODS: A total of 489 participants completed the first of three annual surveys. A disability group (DG) consisted of 404 graduates and 85 graduates constituted a comparison group (CG). RESULTS: Positive employment and economic outcomes were reported. DG apprenticeship graduates and DG traineeship graduates who obtained full-time employment following graduation had outcomes comparable with CG participants. The findings identified many other similarities in outcomes between the DG and CG.CONCLUSIONS: There are strong graduate employment and related outcomes for apprentices and trainees with disabilities. Findings from the second and third waves will shed further light on the sustainability of outcomes over time.